Changing Union-Party Relations in Canada: The Rise of the Working Families Coalition - Walchuk, Bradley (Labor Studies Journal, 2010)
The traditional understanding of union-party relations in Canada suggests that the social-democratic New Democratic Party (NDP) is the party of organized labour. Reality, however, dictates that this is no longer the case. This paper examines the rise of the Working Families Coalition (WFC) and its effects on union-party. While popular rhetoric suggests that the Coalition is simply a front for the Liberal Party, a more in-depth analysis suggests otherwise. The paper suggests that the emergence of the WFC has significantly changed the union-party relationship in Ontario and consequently has altered the political strategy of the labour movement.